P112 Serum inflammatory biomarkers as predictors of treatment outcome in pulmonary tuberculosis. (15th November 2016) - Ritchie, A; Singanayagam, A; Manalan, K; Connell, D; Chalmers, J; Sridhar, S; Lalvani, A; Wickremasinghe, M; Kon, OM
Abstract : Background: The aim of this study was to evaluate C-reactive protein(CRP), globulin and white cell count as predictors of treatment outcome in pulmonary tuberculosis. Methods: An observational study of patients with active pulmonary tuberculosis was conducted at a tertiary centre. All patients had serum CRP, globulin and white cell count measured at baseline and two months following commencement of therapy. The outcome of interest was requirement for extension of therapy beyond 6 months. Results: There were 226 patients included in the study. Serum globulin >45 g/L was the only baseline biomarker evaluated that independently predicted requirement for therapy extension (OR 3.59 (1.79–7.57; p < 0.001)). An elevated globulin level that failed to normalise at 2 months was also associated with increased requirement for treatment extension(63.9% versus 5.1%;p < 0.001) and had low negative likelihood ratio(0.07) for exclusion of requirement for therapy extension. On multivariable analysis, an elevated globulin that failed to normalise at 2 months was independently associated with requirement for therapy extension (OR 6.12 (2.23–16.80); p < 0.001). Conclusions: Serum globulin independently predicts requirement for treatment extension in pulmonary TB and outperforms CRP and white cell count as a predictive biomarker. Normalisation of globulin at two months following treatment commencement is associated with low risk of requirement for treatment extension.